Determinants of employee satisfaction with career development in the public sector - Fröhlich, Laura (Organizacija (Kranj), 2026)
Background/Purpose: Employee satisfaction with career development is an important factor influencing motivation, commitment, and long-term retention, particularly in the public sector, where career paths are often constrained by legal and institutional frameworks. The purpose of this paper is to analyse employee satisfaction with career development in a selected public institution and to examine the influence of selected demographic and organisational factors. Methods: The study is based on a quantitative empirical research design. Data were collected using a structured questionnaire administered to a sample of 113 employees in a public institution. Due to deviations from normal distribution, non-parametric statistical methods were applied, including the Mann–Whitney U test, the Kruskal–Wallis test, and Spearman’s rank correlation coefficient. Results: The results show that length of service and gender do not have a statistically significant effect on satisfaction with career development. In contrast, material forms of rewards have a stronger positive impact on satisfaction than non-material rewards, which deviates from some prevailing theoretical assumptions. Supervisory support was identified as the strongest predictor of satisfaction with career development. Conclusion: The findings highlight the importance of supervisory support and development-oriented leadership in fostering satisfaction with career development in institutionally constrained public-sector environments and contribute to a better understanding of career development dynamics in Slovenian public institutions.
Keywords: career development; employee rewards; employee satisfaction; javni sektor; karierni razvoj; nagrajevanje zaposlenih; podpora nadrejenih; public sector; supervisory support; zadovoljstvo zaposlenih